1992
DOI: 10.1212/wnl.42.5.985
|View full text |Cite
|
Sign up to set email alerts
|

Stroke subtypes among Chinese living in Hong Kong

Abstract: The Shatin Stroke Registry is a prospective study of all patients admitted with acute stroke to a general hospital in Hong Kong where the population is predominantly Chinese. Each patient was examined by a neurologist and 95.5% of the patients had a brain CT. Of 777 patients included in the study, 44.0% had a cortical/subcortical infarct, 18.5% a supratentorial lacunar infarct, 24.2% a supratentorial intracerebral hemorrhage, 5.8% brainstem/cerebellar infarct, 2.9% a brainstem/cerebellar hemorrhage, and 4.5% a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
45
2
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 0 publications
4
45
2
1
Order By: Relevance
“…[7][8][9][10][11][12][13][14][15][16] Previous studies in China, Hong Kong, Taiwan, and Japan generally found that 23% to 52.2% of strokes were hemorrhagic, [3][4][5][6][21][22][23][24][25] in contrast to only 9% to 18% in whites. [7][8][9][10][11][12][13][14][15][16] In the present study, 29.6% of stroke cases overall in 2000 were hemorrhagic in Chinese populations, which supported the above idea that an ethnic difference existed between Eastern and Western populations.…”
Section: Stroke Subtypes In Chinese Populations Compared With Westernmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15][16] Previous studies in China, Hong Kong, Taiwan, and Japan generally found that 23% to 52.2% of strokes were hemorrhagic, [3][4][5][6][21][22][23][24][25] in contrast to only 9% to 18% in whites. [7][8][9][10][11][12][13][14][15][16] In the present study, 29.6% of stroke cases overall in 2000 were hemorrhagic in Chinese populations, which supported the above idea that an ethnic difference existed between Eastern and Western populations.…”
Section: Stroke Subtypes In Chinese Populations Compared With Westernmentioning
confidence: 99%
“…For example, in the early 1990s, age-adjusted mortality rates (per 100,000) of 56 and 129 were reported for CHD and stroke in China, whereas the corresponding rates for the US Caucasian population were 124 and 28, and those for the UK Caucasian population were 284 and 51 respectively [3]. In addition to differences in prevalence rates, the distribution of arterial atherosclerotic lesions also varies between Oriental and Caucasian populations [4,5]. Furthermore, intracerebral haemorrhage has been reported to be two to three times more frequent in Chinese populations than in Caucasian populations, accounting for 20 to 30% of strokes [5].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to differences in prevalence rates, the distribution of arterial atherosclerotic lesions also varies between Oriental and Caucasian populations [4,5]. Furthermore, intracerebral haemorrhage has been reported to be two to three times more frequent in Chinese populations than in Caucasian populations, accounting for 20 to 30% of strokes [5].…”
Section: Introductionmentioning
confidence: 99%
“…Intracerebral hemorrhage has been reported to be two to three times more frequent in Chinese than in Caucasian populations, accounting for 20 -30% of strokes (6). In 114 nonselected autopsy subjects from Hong Kong, intracranial stenosis was found to be more severe than extracranial stenosis (7).…”
mentioning
confidence: 99%